2017
DOI: 10.1002/mrc.4660
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scaleNMRsimulations in liquid state: A tutorial

Abstract: Liquid state nuclear magnetic resonance is the only class of magnetic resonance experiments for which the simulation problem is solved comprehensively for spin systems of any size. This paper contains a practical walkthrough for one of the many available simulation packages — Spinach. Its unique feature is polynomial complexity scaling: the ability to simulate large spin systems quantum mechanically and with accurate account of relaxation, diffusion, chemical processes, and hydrodynamics. This paper is a gentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…Hyperpolarization of 19 F in 3-fluoro-DL-tyrosine 1 was previously investigated by Kuprov et al [13] and by Gü den-Silber et al [17] Using an argon laser with maximum output power of 25 W Kuprov found an SE of up to 40-fold for 19 F. [13] The authors also observed 1 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 agree well with our results. Gü den-Silber et al showed that aircooled laser diode (10 W) generated photo-CIDNP of 7 mM 3fluoro-DL-tyrosine with 0.2 mM FMN in water even allowed for spatially resolved MRI using a multi chemical shift-selective imaging (mCSSI) sequence.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Hyperpolarization of 19 F in 3-fluoro-DL-tyrosine 1 was previously investigated by Kuprov et al [13] and by Gü den-Silber et al [17] Using an argon laser with maximum output power of 25 W Kuprov found an SE of up to 40-fold for 19 F. [13] The authors also observed 1 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 agree well with our results. Gü den-Silber et al showed that aircooled laser diode (10 W) generated photo-CIDNP of 7 mM 3fluoro-DL-tyrosine with 0.2 mM FMN in water even allowed for spatially resolved MRI using a multi chemical shift-selective imaging (mCSSI) sequence.…”
mentioning
confidence: 91%
“…A well-studied system is 3-fluoro-DLtyrosine, where Kuprov et al found a 19 F 20-to 40-fold signal enhancement after irradiation with an argon laser. [13] This standard approach has the disadvantage that the high intensity of the laser light leads to significant heating of the sample (up to boiling) that may be harmful to biological tissue, thus limiting this otherwise promising technique for biomedical applications. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 physiologically compatible solvents and substrates are indispensable for an in vivo application.…”
mentioning
confidence: 99%
“…[33] Note that second-order effects could be anticipated by observing, from the NMReDATA, that coupling partners present a small difference in chemical shifts. Determining the coupling constants, even in the case of strong coupling and magnetic equivalence, should be possible by spectral simulation and fitting procedures found in SPINACH [21,22] (all kinds of spectra), ANATOLIA [23] (currently only 1D 1 H spectra) or GISSMO. [24] The 2D correlations reported in NMReDATA can also be verified by checking the presence of signals at the coordinates of the chemical shifts of the correlated spins.…”
Section: Validation Of Nmredatamentioning
confidence: 99%
“…Using symbolic expressions of magnetic-field dependent relaxation matrices, the HRR experiments are simulated and measured relaxometry relaxation rates are corrected so that a reliable analysis of the dynamic properties of the system under study can be performed. Thus, the development of tools to simulate spin relaxation for a broad variety of field trajectories is of great interest, in several areas of magnetic resonance [27][28][29]. Here, we present a toolbox that combines two programs.…”
Section: Introductionmentioning
confidence: 99%
“…RedKite has been written in Mathematica (version 12.0) [30] to perform efficiently analytical calculations using the SpinDynamica (version 2.15.1b10) [29] package and the so called "BRW engine" to simplify the computation of relaxation rates [28]. This version of ICARUS has been written in Python (version 3.5).…”
Section: Introductionmentioning
confidence: 99%